2017
DOI: 10.1038/s41598-017-11119-x
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic Chip for High-throughput Blood Cell Depletion to Sort Rare Circulating Tumor Cells

Abstract: Circulating tumor cells (CTCs) are a treasure trove of information regarding the location, type and stage of cancer and are being pursued as both a diagnostic target and a means of guiding personalized treatment. Most isolation technologies utilize properties of the CTCs themselves such as surface antigens (e.g., epithelial cell adhesion molecule or EpCAM) or size to separate them from blood cell populations. We present an automated monolithic chip with 128 multiplexed deterministic lateral displacement device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
150
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(155 citation statements)
references
References 55 publications
4
150
0
1
Order By: Relevance
“…The use of sparse pillar arrays with only several pillar structures and the sieve-based lateral displacement is able to improve the throughput rate in DLD, but it requires an additional adjustment on the array design to balance the pressure to prevent the disruption of the particle separation [94][95][96][97]. Stacking and parallelization of microfluidic DLD devices to multiply the throughput rate have also been reported [37,[98][99][100]. For example, [17].b The application of paper pump to drive the particle separation in an open DLD channel [69].…”
Section: Low Separation Throughputmentioning
confidence: 99%
“…The use of sparse pillar arrays with only several pillar structures and the sieve-based lateral displacement is able to improve the throughput rate in DLD, but it requires an additional adjustment on the array design to balance the pressure to prevent the disruption of the particle separation [94][95][96][97]. Stacking and parallelization of microfluidic DLD devices to multiply the throughput rate have also been reported [37,[98][99][100]. For example, [17].b The application of paper pump to drive the particle separation in an open DLD channel [69].…”
Section: Low Separation Throughputmentioning
confidence: 99%
“…In another work, Fachin et al presented an automated monolithic chip with 128 multiplexed DLD devices containing~1.5 million microfabricated features (12 µm-50 µm) used to exhaust RBCs, platelets and WBCs. It quantified the size and EpCAM expression of over 2500 CTCs from 38 patient samples obtained from breast, prostate, lung cancers, and melanoma and found that neither CTC size nor EpCAM expression can maximize isolation efficiency as many CTCs found were small and expressed lower levels of EpCAM ( Figure 2D) [57]. Au et al presented a two-stage continuous microfluidic chip that separates and recovers viable CTC clusters from blood.…”
Section: Sorting Based On Sizementioning
confidence: 99%
“…Because inertial focusing is dependent on both particle size and the channel geometry, the range of particle sizes that are focused can be controlled, enabling separation of cells by size (Di Carlo, Irimia, Tompkins, & Toner, 2007). While there are many potential applications of inertial focusing for cell separation, the most recent and exciting one has been the isolation of rare CTCs from whole blood with high throughput (Fachin et al, 2017; Ozkumur et al, 2013). In this latest example, inertial focusing is used in conjunction with DLD and magnetic-activated cell sorting to isolate CTCs, independent of size, without labeling the CTCs.…”
Section: Cell Sortingmentioning
confidence: 99%
“…This technology was groundbreaking in its ability to reveal the heterogeneity of CTCs from a single patient. The device was able to recover 99.5% of input CTCs while sorting cells at up to 20 million cells/second (Fachin et al, 2017). …”
Section: Cell Sortingmentioning
confidence: 99%